Theory of Reasoned Action sebagai Prediktor Whistleblowing Intention Pengelola Keuangan di Institusi Pendidikan - Natawibawa, I Wayan Yeremia; Irianto, Gugus; Roekhudin, Roekhudin (Jurnal Ilmiah Administrasi Publik, 2018)
This research was aimed to analyze the perception of financial keepers in school organization on whistleblowing intention and to understand this relationship through Theory of Reasoned Action (TRA). Population of research was 214 persons comprising of 24 principals, 97 vice-principals, 22 school administration heads, 32 treasurers, and 39 financial administration staffs in Public Senior/ Vocational/ Moslem High Schools in Malang City. Census sampling technique was used. Data were collected with questionnaire. There are 192 questionnaires were returned and were completely filled. Multiple regression analysis instrument was used in this research. Result of research indicated that attitude toward whistleblowing and subjective norm are positively affect whistleblowing intention.